Molecular evolution and phylogeographic analysis of wheat dwarf virus - Wei, Shiqing; Liu, Linwen; Chen, Guoliang; Yang, Hui; Huang, Liang; Gong, Guoshu; Luo, PeiGao; Zhang, Min (Frontiers in Microbiology, 2024)
Wheat dwarf virus (WDV) has caused considerable economic loss in the global production of grain crops. Knowledge of the evolutionary biology and population history of the pathogen remain poorly understood. We performed molecular evolution and worldwide phylodynamic analyses of the virus based on the genes in the proteincoding region of the entire viral genome. Our results showed that host-driven and geography-driven adaptation are major factors that affects the evolution of WDV.Bayesian phylogenetic analysis estimates that the average WDV substitution rate was 4.240×10 -4 substitutions/site/year (95% credibility interval, 2.828×10 -4 -5.723×10 -4 ), and the evolutionary rates of genes encoding proteins with virion-sense transcripts and genes encoding proteins with complementary-sense transcripts were different.The positively selected sites were detected in only two genes encoding proteins with complementary-sense, and WDV-barley are subject to stronger purifying selection than WDV-wheat. The time since the most recent common WDV ancestor was 1746 (95% credibility interval, 1517-1893) CE. Further analyses identified that the WDVbarley population and WDV-wheat population experienced dramatic expansiondecline episodes, and the expansion time of the WDV-barley population was earlier than that of the WDV-wheat population. Our phylogeographic analysis showed that the WDV population originating in Iran was subsequently introduced to Europe, and then spread from Eastern Europe to China.